Analisis Prediktor Karakteristik Demografis (Usia, Jurusan, Stambuk) Terhadap Minat Berorganisasi Mahasiswa FIP Unimed - Ade Septiani Siregar; Asima Febrianti Hutauruk; Dita Aulia Saskila Silalahi; Lena Bondar; Nabila Putri Harahap; Syawitri Maharani (CV. Eracita Grup, 2026)
Student participation in organizations is influenced by various factors, yet the specific role of demographic characteristics as predictors remains underexplored empirically at the Faculty of Education, Universitas Negeri Medan. This study aims to examine the effect of these demographic characteristics—specifically age, department, and year of entry (stambuk)—on students’ interest in participating in student organizations. This study employed a quantitative explanatory approach. The sample consisted of 32 students selected using a simple random sampling technique. Data were collected through an online questionnaire distributed via Google Forms and analyzed using multiple linear regression. The results indicate that age, department, and year of entry do not have a significant effect on students’ interest in participating in organizations, either simultaneously or partially. The coefficient of determination shows that demographic characteristics explain only 23.5% of the variance in organizational interest, while the remaining variance is likely influenced by other factors outside the regression model. Therefore, it can be concluded that demographic characteristics are not robust predictors of students' interest in organizations in this specific context.